2020
DOI: 10.1589/jpts.32.422
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed ND:YAG laser combined with progressive pressure release in the treatment of cervical myofascial pain syndrome: a randomized control trial

Abstract: To investigate the effect of pulsed Nd:YAG laser combined with the progressive pressure release technique (PPRT) and exercises in the treatment of myofascial trigger points (MTrPs) in patients with myofascial pain syndrome (MPS). [Participants and Methods] A total of 50 patients with MTrPs in the upper trapezius muscle participated in the study. The patients were randomly assigned to two groups and treated with laser plus PPRT (Laser + PPRT group) or placebo laser and exercises (PL + PPRT group). The laser was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…The authors concluded that HILT significantly reduced pain, compared with physiotherapy [43]. Also, Alayat et al showed that HILT plus pressure release significantly improved the pain intensity and PPT in patients with MTrP in the UT muscle [44]. In line with the present study, Dundar et al showed that HILT significantly improved the pain in patients with trigger points in the trapezius muscle [26].…”
Section: The Effect Of Hilt On the Active Trigger Points Of The Ut Musclesupporting
confidence: 86%
“…The authors concluded that HILT significantly reduced pain, compared with physiotherapy [43]. Also, Alayat et al showed that HILT plus pressure release significantly improved the pain intensity and PPT in patients with MTrP in the UT muscle [44]. In line with the present study, Dundar et al showed that HILT significantly improved the pain in patients with trigger points in the trapezius muscle [26].…”
Section: The Effect Of Hilt On the Active Trigger Points Of The Ut Musclesupporting
confidence: 86%
“…Figure 2 presents the RoB.2 assessment. The randomization process was rated as low risk in 66.7% of the articles [28,29]. The deviations from intended intervention bias was evaluated as high risk in one article [30], some concerns in another [29], and low risk of bias in the other [28], i.e.…”
Section: Pedro and Rob2 Assessment For Individual Rctsmentioning
confidence: 99%
“…The missing outcome data was rated as low risk in two articles, i.e. 66.6% [28,29]. Measurement of the outcome bias was rated as low risk for 100% of the articles [28−30].…”
Section: Pedro and Rob2 Assessment For Individual Rctsmentioning
confidence: 99%
See 2 more Smart Citations